IMPACT OF DIETARY CHITOSAN ON GROWTH PERFORMANCE AND BLOOD BIOCHEMICAL PROFILE OF BROILERS - Tayyaba Qamar; Dr Mahnoor Pervez; Maryam Liaqat; Iqra Yahya; Aneela Khalid (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
In Pakistan, the poultry sector is playing an important role in bridging the gap between the supply and demand for protein. Feed additives are mainly used for improving poultry health and production worldwide. Chitosan is used as a feed additive due to its biological properties such as biocompatibility, antimicrobial, anti-inflammatory activities. The objective of this experiment aimed to examine the effects of dietary chitosan in broiler on growth performance and hematological parameters. One-day old unsexed broiler chicks (Ross-308) with an average initial weight (average 45 ±0.4g body weight) was allotted into three groups. The first group was fed the basal diet and served as the control; the experimental groups 1 and 2 were fed on basal diet supplemented with chitosan at 0.75 and 1.5g/kg diet respectively. The growth performance of broilers was measured in terms of feed intake, body weight gain and feed conversion ratio calculated by pen basis on day 21, 42, and 1-42. The results showed that experimental group 2 supplemented with 1.5g/kg dietary chitosan significantly (P ≤ 0.001) improved the feed conversion ratio. The blood samples for serological and hematological profiles were collected on day 42 and the hematological analysis revealed significant (P ≤ 0.001) increase in the total RBC, hemoglobin, the platelet, HCT, MCH, MCHC and WBC count in experimental groups as compared to control group. The analysis of lipid profile also determined that there is a significant (P ≤ 0.001) lowering of cholesterol, triglycerides and LDL occurs in experimental groups relative to control group. The levels of bilirubin, ALT, Alkaline Phosphate, Urea, Creatinine, Sodium, and Potassium remain unchanged (P ≥ 0.05). It is concluded that chitosan may be used as feed additive as it improves the growth performance and hematological indices of broilers.